Impact of multi factor leadership approach on employee conflict and employee performance in Malaysia - Mehwish, Rashid; Rosmaini, Tasmin; Muhammad, Shafiq (American Scientific Publishers, 2017)
Leadership is the need of today’s business circumstances. Because care of the worker helps to enhance profit. Leader’s quality flourishes the life’s quality1. Followers thinking, approach,conduct and comfort is influenced by Leadership behavior. Development of leader’s abilities and capability is because of the preparation and training, a leader gets to progress, resulting in better leadership. According to 2, organizational and social atmosphere and leader’s interaction in it, makes Leadership multifaceted as also stated by 3, 4.Solving problems and handling crises to manage followers are the characteristics of leadership. Trait, contingency, behavioral, and transformational are the main leadership theories discussed by5. Multi-factor or full range of leadership theory (Transformational, Transactional and Laissez-faire) was developed by 6is a generalized model for diverse cultures, organizations and different management levels as described by7.Multifactor Leadership Questionnaire is frequently used instrument to explore leadership as quoted by numerous authors.